Acute effects of caffeine supplementation on resistance exercise, jumping, and Wingate performance: no influence of habitual caffeine intake - Grgic, J.; Mikulic, P. (European Journal of Sport Science, 2021)
This study explored the influence of habitual caffeine intake on the acute effects of caffeine ingestion on resistance exercise, jumping, and Wingate performance. Twenty-four resistance-trained males were tested following the ingestion of caffeine (3 mg/kg) and placebo (3 mg/kg of dextrose). Participants were classified as low caffeine users (n = 13; habitual caffeine intake: 65 ± 46 mg/day) and as moderate-to-high caffeine users (n = 11; habitual caffeine intake: 235 ± 82 mg/day). Exercise performance was evaluated by measuring: (a) movement velocity, power, and muscular endurance in the bench press; (b) countermovement jump; and, (c) a Wingate test, performed in that order. Two-way repeated-measures ANOVA revealed a significant main effect (p<0.05) for condition in the majority of analyzed exercise outcomes. In all cases, effect sizes for condition favored caffeine and ranged from 0.14-0.97. Mean increases in velocity and power in resistance exercise ranged from 0.02-0.08 m/s and 42-156 W, respectively. The number of performed repetitions increased by 1.2 and jump height by 0.9 cm. Increases in power in the Wingate test ranged from 31-75 W. We did not find significant group × condition interaction effect (p>0.05) in any of the analyzed exercise outcomes. Additionally, there were no significant correlations (p>0.05; r ranged from -0.29 to 0.32) between habitual caffeine intake and the absolute change in exercise performance. These results suggest that habitual caffeine intake might not moderate the ergogenic effects of acute caffeine supplementation on resistance exercise, jumping, and Wingate performance.